Strategic Issues in Information Systems Planning from the Ghanaian Perspective - Ankrah, Ebenezer (International Review of Management and Marketing, 2016)
The banking sector has seen considerable transformation in the 1980s starting from the United States, then Europe and now the global village. This study adopted the survey methodology. The purpose of this study was to determine the key variables in information system planning of six banks in the Greater Accra Region of Ghana. The main objective of the study is to explore the success predictors of strategic information system planning and to investigate the staff participation in IS strategy formulation. The cases investigated were three local banks and three foreign banks. The six banks used were named Bank A, Bank B, Bank C, Bank D, Bank E and Bank F for the sake of anonymity. With adherence to a survey research methodology, this study used the questionnaire instrument. The total number of questionnaire returned was 248 out of 410, presenting a response rate of 60.5%. The findings revealed that, the local banks concentrate on management team and IT department for the formulation of IS strategy. The story is different for that of the foreign banks. For the foreign banks they solely depend on Technology Group for the formulation of IS strategy. From the findings, the local banks indicted that, the most important SISP success factors are resources, IS alignment to the business strategy and staff training and staff involvement. Whilst the foreign banks also indicated that, the most important SISP success factors are resources, organizational and technological changes and top management involvement. Keywords: Information Systems Planning, Information Systems Strategy, Ghana JEL Classification: M1